The Importance of Learning Strategy Planning to Create Effective Learning from the Perspective of Imam As-Syarkawi - Moh. Iqbal Hadzafi; Achmad Muhlis (Penerbit Hellow Pustaka, 2025)
This study aims to analyze Imam As-Syarkawi’s perspective in Al-Ta‘allamu Nadhariyat wat Thabiqat on lesson plan strategies and its relevance to contemporary education. The method applied is library research with a descriptive qualitative approach. The findings reveal that As-Syarkawi emphasizes the importance of planning that aligns with learning objectives, students’ characteristics, and the integration of theory (nadhariyat) and practice (thabiqat). Teachers are viewed as planners, educators, and evaluators who play a central role in directing the learning process. His thoughts remain relevant to modern educational paradigms, particularly the Merdeka Belajar curriculum which highlights collaborative, contextual, and student-centered learning. This study concludes that well-prepared lesson plan strategies can create effective education processes and shape intelligent, virtuous, and competitive generations.